Sigortalılık süresi ve prim ödeme gün sayısını tamamlama suretiyle kıdem tazminatı hakkı ve bu sebeple yapılan feshin sözleşmesel kayıtlara etkisi - (:unkn) unknown (My University, 2013)
İş sözleşmesinin yaşlılık aylığına hak kazanmak için öngörülen yaş dışındaki koşulları yani sigortalılık süresi ve prim ödeme gün sayısını tamamlama nedeniyle feshine bağlı olarak kıdem tazminatına hak kazanma koşulları incelenmektedir. Bu hakkı kullanan kişinin çalışma yaşamından çekilme amacıyla hareket etmesinin gerekip gerekmediği, bu hakkın sadece bir defaya mahsus olup olmadığı, iş sözleşmesinin bu sebeple feshinin sözleşmesel kayıtlara etkisi yasanın hazırlık çalışmaları öğreti görüşleri ve Yargıtay'ın benzer hukuki müesseselere ilişkin içtihadı çerçevesinde ele alınmaktadır.

In this article the qualification conditions for the severance pay depending upon the termination of the employment agreement by reason of fulfilling the insurance period and the number of premium earned days, which are the requirements to be entitled to the old-age pension except the attainment of the retirement eligibility age. In the light of the preparatory work of legislation, the doctrine and the judgments of the Court of Appeal regarding the similar legal institutions, it will be discussed whether it is required to exercise the termination right for the purpose of leaving from the working life or not, and such a right would be exercised one-time or more, while the effect of the termination of the employment agreement for this reason on the contractual clauses will be in detail analysed.
The right of severance pay in case of fulfilling the insurance period and the number of the premiums earned days, and the effect of the termination of employment agreement to be entitled to such a pay on the contractual clauses
Keywords: İktisat; İşletme